WhatsApp in Arabic Writing Skill Learning - Mokoagow, Alfarizi Farhan; Makalalag, Chendra; Annisa, Maryam Nur (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
البحث الحالي يتناول استخدام WhatsApp في تعلم مهارة الكتابة باللغة العربية في المدرسة الثانوية الإسلامية. الهدف الرئيسي هو استكشاف إمكانيات WhatsApp كأداة فعّالة في تعزيز مهارة الكتابة لدى الطلاب في اللغة العربية. يتيح WhatsApp للطلاب والمعلمين التواصل المباشر، ومشاركة مواد التعلم، وتقديم التغذية الراجعة، والتعاون في مهام الكتابة. يتناول البحث أيضاً تصورات الطلاب والمعلمين حول استخدام WhatsApp في سياق تعلم اللغة العربية. الطريقة البحثية المستخدمة هي النهج الكيفي بأسلوب دراسة الحالة. تظهر نتائج البحث أن استخدام WhatsApp في تعلم مهارات الكتابة باللغة العربية لديه أثر إيجابي. يستطيع الطلاب ممارسة الكتابة بشكل تفاعلي باستخدام ميزات WhatsApp مثل الرسائل النصية، والصور، والأصوات، والفيديو. كما يمكنهم أيضاً تلقي التغذية الراجعة مباشرة من المعلم وزملائهم، مما يساعدهم في تحسين مهارة الكتابة لديهم. بالإضافة إلى ذلك، يُيسّر WhatsApp أيضاً المناقشات الجماعية، ومشاركة موارد التعلم، وتقديم الدعم في تعلم اللغة العربية. تظهر تصورات الطلاب والمعلمين حول استخدام WhatsApp في تعلم اللغة العربية أيضاً إيجابية. يرون في WhatsApp أداة فعّالة في تحسين مهارة الكتابة لدى الطلاب. يمكن للمعلمين تقديم التوجيه والدعم في الوقت الفعلي، في حين يشعر الطلاب بالمزيد من التحفيز والمشاركة في عملية التعلم. This research explores the use of WhatsApp in teaching Arabic writing skills at a madrasah aliyah (Islamic high school). The main objective is to investigate the potential of WhatsApp as an effective tool in enhancing students' writing skills in the Arabic language. WhatsApp enables students and teachers to communicate directly, share learning materials, provide feedback, and collaborate on writing tasks. The study also examines the perceptions of students and teachers regarding the use of WhatsApp in the context of Arabic language learning. The research method employed is a qualitative approach with a case study method. The results of this study indicate that the use of WhatsApp in teaching Arabic writing skills has a positive impact. Students can practice writing interactively using WhatsApp features such as text messages, images, voice, and video. They can also receive direct feedback from teachers and classmates, assisting them in improving their writing abilities. Furthermore, WhatsApp facilitates group discussions, resource sharing, and provides support in Arabic language learning. The perceptions of students and teachers regarding the use of WhatsApp in Arabic language learning are also positive. They view WhatsApp as an effective tool in enhancing students' writing skills. Teachers can provide real-time guidance and support, while students feel more motivated and engaged in the learning process.